The Development of Interactive Multimedia using Adobe Animate to Increase Student’s Learning Interest in Electrolyte and Non-Electrolyte Solution Material - Munawwaroh, Putri; Dewi, Fatria; Afrida, Afrida (LPPPI Publishing, 2024)
Education is a process of developing a person's strengths and abilities, in a conscious and planned way to create a learning process and atmosphere that allows students to actively develop their potential. Education provides everyone with the knowledge, abilities, and values they need to face difficulties and challenges in life. In the modern technological era, education and technology are two elements that are increasingly integrated and have an extraordinary impact on human life. The purpose of this study is to find out how effective the use of interactive multimedia using Adobe Animate is to increase students' interest in learning electrolyte and non-electrolyte solution materials. The method used in this study is Literature Review to compare data from several journals relevant to the research topic. This research relies on literacy data search websites, such as Jurnal Sinta, Google Scholar, and Mendeley. The results of the study show that using interactive multimedia using Adobe Animate as a fun learning medium can increase students' interest in learning.